An increased chloride level in hypochloremia is associated with decreased mortality in patients with severe sepsis or septic shock. Issue 1 (December 2017) - Oh, Hyung; Kim, Seung; Kim, Yong; Kim, Eun; Jung, In; Oh, Dong; Jeong, Su; Ku, Nam; Han, Sang; Choi, Jun; Song, Young; Ryu, Dong-Ryeol; et al.
Abstract Only a few observational studies investigated the association between hypochloremia and mortality in critically ill patients, and these studies included small number of septic patients. Also, no study has evaluated the effect of an increase in chloride (Cl− ) concentration in hypochloremia on the mortality. A total of 843 Korean septic patients were divided into three groups based on their baseline Cl− level, and Cox analyses were performed to evaluate the 28-day mortality. Moreover, the change in Cl− level (ΔCl) from baseline to 24, 48, or 72 hour was determined, and Cox analyses were also conducted to evaluate the relationship of ΔCl with mortality. 301 (35.7%) patients were hypochloremic (Cl−  < 97 mEq/L), and 38 (4.5%) patients were hyperchloremic (Cl−  > 110 mEq/L). During the follow-up period, 119 (14.1%) patients died. Hypochloremia was significantly associated with an increased mortality after adjusting for several variables, but an 1 mEq/L increase of ΔCl within 24 hour in patients with hypochloremia was significantly related to a decreased mortality. Caution might be required in severe septic patients with hypochloremia considering their increased mortality rate. However, an increased Cl− concentration might decrease the mortality rate of such patients.